Audit Opinion, KAP, Financial Distress, Audit Fee Regarding Auditor Switching at Indonesian Sharia Banks - Nur Lusi Aprilia; Umi Suswati Risnaeni (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The purpose of this study is to analyze the effect of audit opinion, KAP, financial distress, and audit fees on auditor turnover at Indonesian Islamic banks listed on the Indonesia Stock Exchange in 2020-2024. Secondary data were obtained from financial reports published by the Capital Market on the Indonesia Stock Exchange. The type of research used in this study was hypothesis testing, using the population method. There were seven data populations used as research objects. This study used logistic regression analysis to test the hypothesis. The results show that audit opinion, KAP, and audit fees have a significant effect on auditor turnover with a positive coefficient direction, while financial distress has an insignificant effect on auditor turnover with a negative coefficient direction. Meanwhile, simultaneously, the variables of audit opinion, KAP, and audit fee have a positive and significant effect on auditor turnover.